Right, Left, Straight Ahead? Results of an Empirical Study on Map-Based Orientation in Real Space with Students at the Beginning of Secondary Education - Wrenger, Katja (Journal of Geography Education, 2016)
How do students at the beginning of secondary education proceed while navigating through an urban area using a map? Which geospatial features do they consult for orientation in a map and in real space? And to what extent do these features influence the students' orientation performance? These questions were examined in an explorative study with a focus on fifth-grade students. For this purpose, a preliminary study was carried out in a first step, which is primarily used to generate volunteers. In a second step, orientation performances and strategies as well as geospatial features employed by the students were gathered along a set route through the city center of Münster. The results show that a limited spectrum of strategies is applied. Besides, the subjects use limited information from the map and real space. Correspondingly, the subjects' success is revealed predominantly at those decision points of the route, at which appropriate orientation aids are immediately visible in the map and real space. Furthermore, directional characteristics emerge as influential, while there is no influence regarding configural features (e.g. the number of alternatives at decision points). The study provides fundamental insights into the knowledge and skills of students at the beginning of secondary education in map-based orientation in real space and offers hypotheses and suggestions for future research.
Keywords: orientation, wayfinding, map reading skills, navigation behavior, large scale space